Comparative Analysis of the Physical, Tactical, Emotional, and Mood Characteristics of Under-13 Soccer Players by Performance Level - Aura D. Montenegro Bonilla; Sergio D. Rodríguez Pachón; Víctor Hernández-Beltrán; José M. Gamonales; Markel Rico-González; José Pino-Ortega; Jorge Olivares-Arancibia; Rodrigo Yánez-Sepúlveda; José Francisco López-Gil; Boryi A. Becerra Patiño (Journal of Functional Morphology and Kinesiology)
Background and Objectives: Soccer is a sport characterized by various unpredictable situations in which physical abilities are associated with athletic performance. There are several capabilities that young soccer players must develop to adapt to the needs of the competition. This study analyzes the physical characteristics, tactical knowledge, emotional intelligence, and mood states of youth soccer players at different competitive levels. Materials and Methods: The sample consisted of 36 male soccer players with an average age of 12.65 ± 0.48 years, weight of 44.92 ± 7.49 kg, and height of 157.2 ± 0.08 cm. A cross-sectional correlational study design was selected. Inferential analysis was conducted via the RV coefficient to assess relationships between groups. Two-sample tests (Student’s t test or the Mann–Whitney U test) were used to assess the distribution of the samples. Standardized mean differences (i.e., Cohen’s d) were calculated as effect sizes. Results: For the yo-yo intermittent endurance test level 1, the Premier category showed higher speed (p = 0.01, d = 0.40) and superior estimated VO2max (p = 0.01, d = −0.91). The statistically significant variables included the hamstring strength exercise of the hamstrings for the angle of rupture (p = 0.04, d = −0.04, d = −0.72), the COD-Timer 5-0-5 for contact time—5-0-5 (ms) (p = 0.04, d = 0.69) and 10 m—5-0-5 (s) (p = 0.02, d = 0.79), tactical knowledge of in-game performance (p = 0.01, d = −1.19), support level (p = 0.01, d = −1.27), decision-making ability (p = 0.01, d = 0.59), melancholy (p = 0.01, d = 0.59), confusion (p = 0.01, d = 0.56), and emotional intelligence (p = 0.04, d = 0.77). The Premier category presented slightly higher averages than did category A. In the assessment of running-based anaerobic sprint test power (p < 0.05, d = 0.83) and mood states (p < 0.05, d = 0.59), players in category A presented higher results. Conclusions: The performance capacity of youth soccer players encompasses a multidimensional complexity that includes physical, tactical, emotional, and psychological aspects, which vary among players of the same age.